Respuesta :
Answer:
D (6,1)
Step-by-step explanation:
[tex]x + 3y = 9[/tex]
[tex]y = x-5[/tex]
When [tex]y = x-5[/tex], it means we don't need to move the variables to the left side and right side. We can use [tex]y = x-5[/tex] to substitute into the first equation [tex]x + 3y = 9[/tex] directly.
[tex]x + 3y = 9[/tex]
[tex]x+3(x-5)=9[/tex]
[tex]x+3x-15=9[/tex]
[tex]4x=9+15[/tex]
[tex]4x=24[/tex]
[tex]x=6[/tex]
When x=6, we can substitute the value of x into any equation whatever you want. You can choose [tex]x + 3y = 9[/tex] or [tex]y = x-5[/tex]. I choose [tex]y = x-5[/tex] is easier to get the value of y.
When x=6, substitute into [tex]y = x-5[/tex]
[tex]y=6-5[/tex]
[tex]y=1[/tex]
Hooray, now you have the value of x and y which are x=6 and y=1.
I hope you will understand the answer.
You can ask any question here if you still cannot get the point. Don't be shy.